Pagiphora aschei Kartal (Hemiptera: Cicadidae) from Crete (Greece) - distribution and description of its song - Trilar, Tomi (Acta entomologica slovenica (Ljubljana), 2012)
Using recording equipment for sonic range we recorded the calling song of Pagiphora aschei Kartal 1978 that can be found in the Greek island of Crete and in the Antalya Province of Turkey. In Crete, P. aschei is widely distributed and common from the seacoast up to 600 m a. Nevertheless, the song of this species had not been described until now. The calling song structure is characteristic and easily distinguishable from the songs of related cicadas. Typical for the calling song are two song patterns, monotonous repetition of short echemes and continuous song. The calling song is made of three phrases (A, B, C). Phrase A consists of short echemes, phraseB has an introductory part of continuous song, which switches without any interruption to sequence of short echemes, and phrase C consists of continuous song with characteristic amplitude envelope. This species-specific calling song pattern is compared with known songs of other Pagiphora species.
Keywords: bioacustics; bioakustika; calling song; Cicadidae; Mediterranean Basin; Pagiphora aschei; pozivni napev; singing cicadas; Sredozemlje; škržadi